2018
DOI: 10.1016/j.jinorgbio.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the thiosemicarbazonecopper(II) reaction with glutathione. Activity against colorectal carcinoma cell lines

Abstract: Thiosemicarbazones (TSCs), and their copper derivatives, have been extensively studied mainly due to the potential applications as antitumor compounds. A part of the biological activity of the TSC-Cu complexes rests on their reactivity against cell reductants, as glutathione (GSH). The present paper describes the structure of the [Cu(PTSC)(ONO)] compound (1) (HPTSC=pyridine-2-carbaldehyde thiosemicarbazone) and its spectroscopic and magnetic properties. ESI studies performed on the reaction of GSH with 1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 123 publications
(108 reference statements)
5
8
0
Order By: Relevance
“…When we investigated the role of redox activity, opposing to the current theory of activation by reduction (16,20,27), nanomolar-active TSCs were characterized by copper(II) complexes with higher stability and less efficient reduction by reducing agents. This observation is in line with other studies such as from Garcia-Tojal et al, and from Santoro et al who both found slower reduction by GSH in the case of the copper(II) complex of Dp44mT, as compared to the copper(II) complexes of Triapine and FTSC/PTSC (11,44). Moreover, for both Triapine as well as FTSC, reduction of the copper(II) complex resulted in efficient binding of the copper(I) ion to GSH leaving a metal-free ligand able to interact with other metal ions such as iron or zinc (44).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…When we investigated the role of redox activity, opposing to the current theory of activation by reduction (16,20,27), nanomolar-active TSCs were characterized by copper(II) complexes with higher stability and less efficient reduction by reducing agents. This observation is in line with other studies such as from Garcia-Tojal et al, and from Santoro et al who both found slower reduction by GSH in the case of the copper(II) complex of Dp44mT, as compared to the copper(II) complexes of Triapine and FTSC/PTSC (11,44). Moreover, for both Triapine as well as FTSC, reduction of the copper(II) complex resulted in efficient binding of the copper(I) ion to GSH leaving a metal-free ligand able to interact with other metal ions such as iron or zinc (44).…”
Section: Discussionsupporting
confidence: 93%
“…In good agreement with the literature (11), no time-dependent spectral changes were observed in the case of AA which suggests that these metal complexes cannot be reduced by AA under the applied conditions (see Suppl. Figure 5).…”
Section: Reduced Reduction Rate Of Copper(ii) Complex Has a Strong Impact On Tsc Activitysupporting
confidence: 91%
See 3 more Smart Citations